LUMiC® endoprosthesis for pelvic reconstruction: A Canadian experience. Issue 4 (22nd December 2022) - Rizkallah, Maroun; Ferguson, Peter C.; Basile, Georges; Kim, Paul; Werier, Joel; Wilson, David; Turcotte, Robert
Abstract: Background and Objectives: The LUMiC® prosthesis was introduced to reduce the mechanical complications encountered with periacetabular reconstruction after pelvic tumor resection. Few have evaluated the outcomes associated with its use. Methods: A retrospective study from five Orthopedic Oncology Canadian centers was conducted. All patients with a LUMiC® endoprosthesis were included. Their charts were reviewed for surgical and functional outcomes. Results: A total of 16 patients were followed for 28 months (3–60). A total of 12 patients (75%) had a LUMiC® after a resection of a primary sarcoma. Mean surgical time was 555 min. Four patients (25%) had a two‐stages procedure. MSTS score was 60.3 preoperatively and 54.3 postoperatively. Patients got a dual mobility bearing and the silver coated implant was used in 7 patients (43.7%). Five patients (31.3%) underwent capsular reconstruction using a fabric. Silver‐coating was not found to reduce infection risk ( p = 0.61) and capsuloplasty did not prevent dislocation ( p = 0.6). Five patients had peroperative complications (31.3%). Eight patients (50%) had an infection including all four with two‐stages surgery. Dislocation occurred in five patients (31.3%) whereas no cases of aseptic loosening were reported. A total of 10 patients (62.5%) needed a reoperation. Conclusion: LUMiC® endoprosthesis provides low rates of aseptic loosening on medium‐term follow‐up. Infection and dislocation are common complications but we were unable to show benefits of capsuloplasty and silver‐coated implants.